Construction, characterization, and visible light-assisted photocatalytic degradation behaviour of Graphitic carbon nitride (g-C3N4) photocatalyst - hanan hashim (Misan Journal of Engineering Sciences)
photocatalysis is a promising process for decomposing organic pollutants in wastewater. Choosing an appropriate photocatalyst that is effective under visible light is essential for environmental applications. In this study, graphite carbon nitride(g-C3N4) synthesized by the thermal calcination process, characterization by various characterization analysis techniques such as Field Emission Scanning Electron Microscopy (FE-SEM), X-ray diffraction (XRD), UV–vis diffuse reflection spectroscopy (DRS), and photoluminescence (PL) spectrum, the DRS analysis shows the boundaries of absorbing light by g-C3N4 to be lies in the visible light region with aband gap of (2.7ev). Methylene blue (MB) and Rhodamine B (Rh.B) degradation activity in an aqueous solution was investigated over a constructed visible-light-driven g-C3N4 photocatalyst. Within 120 min visible light irradiation under condition of PH of 6.7, dyes concentration of 30 ppm, and photocatalyst dose of 0.1 g/l, under constant temperature and pressure was (80.3%) and (81.6%) for MB and Rh.B dyes, respectively. The photocatalytic degradation activity’s kinetic reaction of pseudo-first order has been studied. Also, the mechanism has been investigated in this study